2017
DOI: 10.1002/stc.2123
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stationary and walking people on vertical dynamic properties of a lively lightweight bridge

Abstract: Summary This paper investigates the effect of both stationary and walking people on vertical dynamic characteristics of structures based on an experimental program. A lively lightweight bridge was designed and constructed for the experiments. Dynamic properties of the bridge are obtained based on ambient vibration testing method. Stationary tests of straight knees and bent knees postures under different crowd sizes were performed using heel‐impact method. Synchronized walking tests were conducted considering w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…The study is carried out on the basis of the following modelling assumptions: Even though it is widely accepted that human–structure interaction (HSI) occurs when pedestrians walk on a flexible structure and a great number of studies have been recently devoted to this issue (e.g., literature), there is still great uncertainty about how to model HSI. Therefore, HSI is neglected in this study.…”
Section: Modelling Approachmentioning
confidence: 99%
“…The study is carried out on the basis of the following modelling assumptions: Even though it is widely accepted that human–structure interaction (HSI) occurs when pedestrians walk on a flexible structure and a great number of studies have been recently devoted to this issue (e.g., literature), there is still great uncertainty about how to model HSI. Therefore, HSI is neglected in this study.…”
Section: Modelling Approachmentioning
confidence: 99%
“…Generally, there are two main aspects of HSI 18 : (a) the effect of occupants on the dynamic characteristics and response and (b) the effect of vibration on the interaction force induced by occupants. The latter occurs because humans tend to emulate their behavior with surrounding people and the vibrating system tends to follow the excited motion 18 …”
Section: Introductionmentioning
confidence: 99%
“…A variety of experimental studies have been conducted to explore how occupants influence the dynamic properties of structures, especially footbridges 13,19 . For example, Zivanovic et al 20 and He and Xei 18 investigated the effects of stationary and walking humans on vertical dynamic responses of footbridges based on an experimental program. Zivanovic et al stated that the structural damping of a footbridge with stationary or walking occupants increased with the increasing number of people.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the relatively lower modal mass of the FRP bridges results in increased liveliness (i.e., accelerance) compared to the non-FRP bridges. He and Xie [3] studied the dynamic properties of a lightweight steel-concrete composite bridge under walking people, and found that the pedestrian-to-bridge mass ratio plays a key role in the dynamic properties of the human-bridge system. From the results of these studies, it can be seen that neglecting the effect of human-structure interaction (HSI), as is done in many current guidelines, will lead to inaccurate vibration prediction for lively lightweight structures [4].…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%